Workplace Happiness and Transformational Leadership as Drivers of Organizational Commitment in Networked Work Environments - Desara, Edwin; Yasmin, Devi (Celebes Scholar pg, 2024)
This study examines the influence of workplace happiness and transformational leadership on organizational commitment within PT Bumi Mekanika Utama. Using a quantitative design with saturated sampling of 42 employees, data were analyzed through multiple linear regression, correlation tests, and significance testing. The results demonstrate that workplace happiness exerts a significant positive effect on organizational commitment, while transformational leadership alone does not. However, when combined, both variables significantly strengthen commitment, indicating that leadership effectiveness depends on the presence of supportive and happiness-enhancing work conditions. These findings highlight the primacy of workplace happiness as the foundation of organizational loyalty, with leadership playing a complementary role when aligned with employees lived experiences. Practically, organizations should prioritize recognition, fairness, and social support as strategies to foster happiness, thereby enabling leaders to amplify commitment through transformational behaviors.